Covid-19 vs Social Protection Case Study of Declining Competitiveness, Information & Communication Technology Adoption in Indonesia - Maria Katje Tupamahu (International Journal of Artificial Intelligence Research, 2022)
The main objective of this study is to examine the problem of declining competitiveness in Indonesia during the period of the spread of the Covid-19 pandemic. Based on WEF assessment, there are  five main pillars (of the 12 pillars) of Indonesia's competitiveness decreased such as Adoption of Information and Communication Technology (ICT Adoption), Health, Skills, Labor Market, and Product Market, and affected  the competitiveness level  slump  down under three other ASEAN Countries, namely Singapore, Malaysia and Thailand.  The research method used is qualitative model with data collection techniques applied observation, interviews, and documentation studies (published by competent state institutions). The results  showed that the Covid-19 outbreak has proven to be the cause of the weakening of the socio-economic sector, followed by poor implementation of social protection policies implemented by the government unable to suppress the spread of the  Covid-19 pandemic, and then cause of declining competitiveness in Indonesia's.